Happy Birthday Bad Kitty - Bruel, Nick (New York : Roaring Brook Press, 2020)
It's Bad Kitty's birthday, and guess who's on the guest list? Chatty Kitty, Strange Kitty, Stinky Kitty, and her other neighborhood pals.
Keywords: Cats -- Juvenile fiction; Birthdays -- Juvenile fiction; Parties -- Juvenile fiction; Cats -- Fiction; Birthdays -- Fiction; Parties -- Fiction